Effect of Indium Content on the Microstructure, Mechanical Properties and Corrosion Behavior of Titanium Alloys - Mi-Kyung Han; Jae-Bong Im; Moon-Jin Hwang; Bong-Jun Kim; Hae-Young Kim; Yeong-Joon Park (Metals, 2015)
Ti-xIn (x = 0, 5, 10, 15 and 20 wt%) alloys were prepared to investigate the effect of indium on the microstructure, mechanical properties, and corrosion behavior of titanium with the aim of understanding the relationship between phase/microstructure and various properties of Ti-xIn alloys. The Ti-xIn alloys exhibited a lamellar α-Ti structure at an indium content of up to 20 wt%. High-resolution TEM images of the Ti-xIn alloys revealed that all the systems contained a fine, acicular martensitic phase, which showed compositional fluctuations at the nanoscopic level. The mechanical properties and corrosion behavior of Ti-xIn alloys were sensitive to the indium content. The Vickers hardness increased as the In content increased because of solid solution strengthening. The Ti-xIn alloys exhibited superior oxidation resistance compared to commercially pure Ti (cp-Ti). Electrochemical results showed that the Ti-xIn alloys exhibited a similar corrosion resistance to cp-Ti. Among the alloys tested, Ti-10In showed a potential for use as a dental material.